2015
DOI: 10.1016/j.actatropica.2015.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Redescription of Spirura guianensis (Nematoda: Spiruridae) from a rare South American Gracile Opossum

Abstract: Spirura genus Blanchard, 1849 comprise of nematode parasites that infect primate and marsupial species. Although several taxonomical studies have shown that the infection by this species occurs primarily in the esophagus of primates, evidence for the occurrence of these parasites in other hosts (marsupials, rodents and bats) has become the subject of investigation by several groups. In this work, we describe the presence of Spirura guianensis Ortlepp, 1924 in the marsupial Gracilinanus agilis (Marsupialia: Did… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 27 publications
(37 reference statements)
0
0
0
Order By: Relevance
“…Similarly, Quentin (1973), when studying Spirura guianensis (Ortlepp, 1924) (Spiruridae), described 2 amphids, 4 cephalic papillae, and 4 external labial papillae, the latter hidden under the buccal cadre. SEM studies of S. guianensis by Torres et al (2015) only revealed the amphids and cephalic papillae. Based on light microscopy, Pence et al (1978;fig.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Quentin (1973), when studying Spirura guianensis (Ortlepp, 1924) (Spiruridae), described 2 amphids, 4 cephalic papillae, and 4 external labial papillae, the latter hidden under the buccal cadre. SEM studies of S. guianensis by Torres et al (2015) only revealed the amphids and cephalic papillae. Based on light microscopy, Pence et al (1978;fig.…”
Section: Discussionmentioning
confidence: 99%